Design of personal development tool (AB-Reflex@) using NLP principles - Nurul 'Amirah 'Izzati Binti Noorazmi (2023)
In a daily life of human nature, communications among the people indeed important in order to understand each other's needs. This nature is also applied between the students and lecturers. But the problems in this nature is that, the different behaviours and characters of people can lead to miscommunication and misunderstandings among them. This is because, people themselves cannot understand what others need and want words to others. This problem can lead to stress by not understanding other people's needs. The improvement of AB-Reflex@ tool has tested which is to beat the stress level of undergraduates in UNITEN. Additionally, the best system in light of mix between NLP, EFT, perfect breathing, The Silva Method, hypnosis and reflexology has been recognized.